A Case of Appendiceal Goblet Cell Carcinoid Tumor: Getting it right under the Microscope - Kang, Waye Hann; Abdul Wahab, Norasyikin; Kamaruddin, Nor Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2020)
Goblet cell carcinoid (GCC) is a rare neoplasm of the vermiform appendix and can be mistaken as a typical neuroendocrine tumour (TNET). The natural history of this disease is more aggressive compared to TNETs and requires a more aggressive approach. We report a case of a 37-year-old male who was initially diagnosed with TNET, but subsequently revised as Tang’s A GCC. He underwent appendectomy and right hemicolectomy. Aside from a persistently elevated carcinoembyrogenic antigen (CEA) result, his 18F-fluorodeoxyglucose (FDG) PET/CT and a 68-Gallium DOTATATE PET/CT scan showed no FDG or DOTATATE avid lesions.